Aspirin use for cardiovascular disease prevention in the uninsured population. (June 2020) - Liu, Nina; Mathews, Adithya; Swanson, Justin; Mhaskar, Rahul; Mathews, Akshay; Ayoubi, Noura; Mirza, Abu-Sayeef
Introduction: Aspirin is an effective anti-inflammatory and antiplatelet agent as an irreversible inhibitor of cyclooxygenase. In 2016, the U.S. Preventive Services Task Force recommended aspirin for primary prevention of cardiovascular disease in patients aged 50–69 years with a 10% or greater 10-year cardiovascular disease risk. Current guidelines for patients with prior myocardial infarction or coronary artery disease recommend aspirin use for the secondary prevention of cardiovascular disease. Due to the lack of literature describing adherence to these recommendations in the uninsured patient population, we studied aspirin use for cardiovascular disease prevention in free medical clinics. Methods: We conducted a cross sectional study of uninsured patients who visited nine free medical clinics in 2016–2017. Data from the records of 8857 patients were combined into a database for analysis. 10-year Framingham risk scores for coronary artery disease were calculated for the 50–69-year-old population to evaluate which patients qualified for aspirin usage. Aspirin use was assessed for patients with prior myocardial infarction or coronary artery disease. Results: In total, 1443 patients met the criteria to take aspirin for primary prevention of cardiovascular disease, but just 17% of these patients aged 50–59 years were on the medication. About 15% of the patients aged 60–69 years were taking aspirin. Of the 297 patients who had prior myocardial infarction or coronary artery disease, 50% were taking aspirin for secondary prevention. Conclusion: Among the uninsured population, there are low rates of aspirin use for risk reduction of cardiovascular disease. This study demonstrates that improvements are needed to increase adherence to current guidelines and address barriers uninsured patients may face in maintaining their cardiovascular health.